Effect of Gold Nanoparticles on the TLR2-Mediated Inflammatory Responses Induced by Leptospira in TLR2-Overexpressed HEK293 Cells - Kanidta Sooklert; Chawikan Boonwong; Pattama Ekpo; Rojrit Rojanathanes; Kanitha Patarakul; Chintana Chirathaworn; Sasin Thamakaison; Amornpun Sereemaspun (Nanomaterials, 2020)
Leptospira infection can cause potential hazards to human health by stimulating inflammation, which is mediated mainly through the Toll-like receptor 2 (TLR2) pathway. Gold nanoparticles (AuNPs) are promising for medical applications, as they display both bioinert and noncytotoxic characteristics. AuNPs have been shown to have the ability to modify immune responses. To understand the in vitro immunomodulatory effect of AuNPs in a Leptospira infection model, the activation of TLR2 expression was examined in HEK-Blue-hTLR2 cells treated with Leptospira serovars and/or AuNPs (10 and 20 nm). The ability of AuNPs to modulate an inflammatory response induced by Leptospira was examined in terms of transcript expression level modulation of three proinflammatory cytokines (tumor necrosis factor-α, interleukin (IL)-1β and IL-6) using two-stage quantitative real-time reverse transcriptase PCR. The results revealed that the administration of 10 nm AuNPs could augment the Leptospira-induced TLR2 signaling response and upregulate the expression of all three cytokine gene transcripts, whereas the 20 nm AuNPs attenuated the TLR2 activation and expression of proinflammatory cytokines. This indicates that AuNPs can modulate inflammatory parameters in Leptospira infection and different-sized AuNPs had different immunomodulatory functions in this model.